Lampião, Lages, Lombroso: the autopsy of the bandit king of the Brazilian backlands - Charles André; Laura Minc Baumfeld André (Arquivos de Neuro-Psiquiatria)
ABSTRACT Lampião, the most infamous Brazilian brigand leader, was killed and decapitated during an ambush in 1938. The Alagoas police coroner, Dr. José Lages Filho, performed an autopsy of his head. Strongly biased toward the anthropologic ideas of the famous Italian psychiatrist and criminalist Cesare Lombroso, the examination found only a few of the so-called criminal inborn traits. The Lombrosian doctrine and a number of related theories strongly influenced medical and political reasoning in the first half of the 20th century. Modern genetic and neuroscientific studies are still looking for the potential biological roots of misbehavior and criminality.